Meningitis-Retention Syndrome as a Presentation of West Nile Virus Meningitis. (31st July 2013) - Mankongpaisarnrung, Charoen; Laengvejkal, Pavis; Argueta, Erwin; Limsuwat, Chok; Sutamtewagul, Grerk; Nugent, Kenneth
Abstract : A 26-year-old previously healthy man presented with fever, urinary retention, nuchal rigidity, and hyperreflexia but with a clear sensorium. His initial spinal fluid results were consistent with aseptic meningitis from West Nile virus infection, and this was confirmed by serological studies on blood and cerebrospinal fluid. Computed tomography and magnetic resonance imaging studies were unremarkable. He received supportive care and urinary catheterization to prevent bladder injury from overdistension. He was discharged home without recurrence of urinary retention after five days of hospitalization. Therefore, this case report describes the first case of West Nile virus meningitis in a patient with the meningitis-retention syndrome.